O papel da narrativa digital para comunicação no cuidado de pessoas com demência - Silva, Paula Fernanda Carlos da (2019)
Considering the epidemiologic transition, dementia has become a paramount issue in public health due to its high prevalence and the gravity of its consequences. In this context, the use of Information and Communication Technologies (ICT) could provide support for digital narratives as a communication tool for a patient with dementia, family members and caregivers. Objective: To explore the issues of communication with formal and informal caregivers of the persons with dementia in the context of long-term care home and home / community context. Method: The present study is an international collaboration project with the project "When TiME matters: digital narrative in home care environments" between researchers from UFSCar and the University of Surrey (UK), in two parts. The first part is a case study in a long-term care institution (ILPI) located in the countryside of the state of São Paulo, Brazil, with caregivers from the staff, older person with dementia and family members who used digital narratives for a one-month trial period. The second part was an interview qualitative study with 10 end-users (formal and informal carers) who work with home care for people with dementia. Results: The results point to the social nature of technology and the importance of the role of the caregiver as facilitator in this process. The results of the case study demonstrated that in general, the technology was more useful in facilitating richer conversations with residents and other participants, as well as stimulating greater expressiveness and creativity in the person with dementia. Furthermore, the results found in the second study showed enthusiasm for adoption of digital narratives as a form of multimedia communication between people with dementia and their caregivers, as well as identifying requirements and needs in communication and emphasizing the importance of inclusive social media in the context of dementia.